Dalhuisen on transnational and comparative commercial, financial and trade law. Volume 3, Transnational contract law - Dalhuisen, J. H. (Jan Hendrik) (London [England] : Hart Publishing, 2022)
"It stands alone in its field not only due to its comprehensive coverage, but also its original methodology. Although it appears to be a weighty tome, in fact, in light of its scope, it is very concise. While providing a wealth of intensely practical information, its heart is highly conceptual and very ambitious... likely to become a classic text in its field." ( American Journal of Comparative Law ) Volume 3 of this new edition deals with the transnationalisation of contract law. It compares common law and civil law concepts, noting the origin of the one in commercial law and of the other in consumer law, and identifies the different attitudes to protection, risk management, and risk distribution. The volume also explores future directions in international commerce and finance, as well as the potential, effects, and challenges of e-commerce, the blockchain, and the emergence of the smart contract. The complete set in this magisterial work is made up of 6 volumes. Used independently, each volume allows the reader to delve into a particular topic. Alternatively, all volumes can be read together for a comprehensive overview of transnational comparative commercial, financial and trade law."--
1. General 1.1 Introduction 1.2 Formation of Contracts in Civil and Common Law 1.3 The Normative Interpretation Technique in Practice: The Civil Law Notion of Good Faith, the Common Law Alternatives, Liberal Interpretation and the Role of Other Sources of Private Law 1.4 Performance of the Contract, Defences, Default, Excuses, Termination 1.5 Privity of Contract 1.6 The UNIDROIT and European Principles of Contract Law. The Vienna Convention and UCC Compared. The Draft Common Frame of Reference in the EU and the Draft EU Regulation on a Common European Sales Law -- 2. Contracts for the International Sale of Goods 2.1 The Main Aspects of the International Sale of Goods 2.2 Ancillary Arrangements in International Sales. The Role of Intermediaries and Documents 2.3 The Uniform International Sales Laws. The Vienna Convention or CISG -- 3. Contractual Agency 3.1 The General Notion of Agency 3.2 International Aspects of Agency
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Contracts (International law); Commercial law; Electronic books